2010
DOI: 10.1007/s10641-010-9639-4
|View full text |Cite
|
Sign up to set email alerts
|

Using otoliths to estimate age and growth of a large Australian endemic monocanthid, Nelusetta ayraudi (Quoy and Gaimard, 1824)

Abstract: Nelusetta ayraudi (the ocean leatherjacket) is an endemic Australian monacanthid species distributed from North West Cape (Western Australia) south to southern Queensland. The commercial and recreational fisheries targeting Nelusetta ayraudi have expanded substantially along the coast of New South Wales (NSW) in recent years but there exists little biological information on which to base effective management of this growing fishery. World-wide, only a few studies have aged monacanthids. Of these, researchers h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…In conclusion, this research describes the life‐history traits of a common monacanthid species in Australasian waters, M. scaber . The life‐history parameter estimates presented here indicate small differences between the sexes in growth, but substantial differences in lifespan and mortality, as seen in other species of the same family (Miller et al., ). More importantly, M. scaber is the longest‐living monachantid species described so far and possibly the oldest documented for the entire suborder.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…In conclusion, this research describes the life‐history traits of a common monacanthid species in Australasian waters, M. scaber . The life‐history parameter estimates presented here indicate small differences between the sexes in growth, but substantial differences in lifespan and mortality, as seen in other species of the same family (Miller et al., ). More importantly, M. scaber is the longest‐living monachantid species described so far and possibly the oldest documented for the entire suborder.…”
Section: Discussionsupporting
confidence: 65%
“…Miller et al . () reviewed reported longevity for species of the family Monacanthidae and found a maximum recorded age of 9 years, attained by both N. ayraud and Thamnaconus septentrionalis (Günther 1874). Although the maximum age of M. scaber males recorded in this study is consistent with the lifespan reported for other monacanthids, females are clearly longer lived.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their ubiquitous presence on reefs, and their conspicuous nature, there is little knowledge of the biology and demography of monacanthids [ 48 ]. Some are known to have very small home ranges on reefs [ 50 ], whilst the largest, endemic species Nelusetta ayraudi forms the basis of a significant fishery in sub-tropical and temperate shelf waters [ 51 ]. The labrids of temperate reefs are much better known for their hermaphroditism and social organisation [ 49 ], territoriality or small home ranges on reefs [ 52 ], niche partitioning [ 53 ] and plasticity in diet [ 54 ].…”
Section: Discussionmentioning
confidence: 99%